Analysis of The Theory of Justice in Insurance Business in Indonesia - DEWI, Ni Luh Putu Yuni Sartika; BAGIASTRA, I Nyoman (Indonesia Strategic Sustainability, 2025)
In carrying out its function as a financial protector in the future, the insurance business must be based on justice to create a healthy relationship between customers and insurance companies. Justice in the insurance business is the main foundation of a healthy and useful insurance industry in Indonesia, if there is no justice then public confidence can be disturbed and trust in the insurance business can be reduced due to the perception of injustice. Justice is very necessary because the low level of understanding of the Indonesian people about insurance products is the main cause of injustice in the insurance service business. This situation is because insurance agents who do not have integrity do not explain the contents of the policy transparently to prospective customers. Based on the above thoughts, the main problem is, first, is the application of the Indonesian insurance agreement justice standard in accordance with the theory of justice? Second, How is the Implementation of Theory in Overcoming Conflicts Between Insurance Companies and Customer Justice in Insurance Companies?